The Influence of Aggregates on Punching Shear Resistance of Slabs-Without Shear Reinforcement - Amin, Rizgar (Basrah Journal for Engineering Sciences, 2016)
The choice of aggregate type in producing reinforced concrete depends on the availability of the source sometimes and the intended concrete requirements like lightweight or normal aggregate concrete or high strength concrete. The punching shear resistance is being considered to be influenced by numbers of parameters including aggregate size and types. These parameters have not accounted in most of codes of design and have given a little attention by researchers. Most of available knowledge are based on outcomes from experimental works on beams. In this paper, the considerable slab tests without shear reinforcement are collected from literature in which aggregate types and sizes are given and they were failed in punching. The test results are compared to those calculated by ACI, EC2 and CSCT. The deficits of shear resistance are found clear where high compressive strength is combined with reinforcement ratio.